Gaita Zuliana's Confrontation with Hugo Chávez in Venezuela: 1999-2003. Issue 2 (3rd April 2021) - Andrade, Gabriel
ABSTRACT: Despite his popularity throughout his tenure as President of Venezuela, Hugo Chávez's populist style aroused confrontation. This confrontation took place in media, and music was not spared. One particular musical genre, gaita zuliana, was used as an expression of dissatisfaction with Chávez's policies and attitudes. This article analyzes the most relevant protest gaitas composed in a relatively short period of time (1999–2003) by the bands Gran Coquivacoa, Koquimba, and Barrio Obrero. Although in subsequent years protest gaitas all but disappeared, the creative wave of protest gaita in this period still resonates today, as Venezuelans still listen intently to these songs.